The Social Change of Barru District Society Due to the Construction of the Makassar - Parepare Railway Line - Darwis, S Jailany; Banowati, Eva; Husain, Fadly (JESS (Journal of Educational Social Studies), 2020)
Indonesia that continued to change over time will no doubt affect the aspects of life. Aspect that could provide sustenance was the need of transportation through the construction of the Makassar - Parepare railway line. The goal was to know the social changes and adaptation patterns of children when social changes occurred as a result of the construction of the Makassar-Parepare railway. This study used qualitative method with descriptive analysis. The informants of the study were; 1) PPK Railway Development of South Sulawesi, 2) Affected communities, 3) Head of BPD in Ajakkang village, and 4) Head of Polewali environment. The data collection technique of this study were interviews, observation, and documentation. The results is construction of the Makassar - Parepare railway led a social change that could be seen based on the process and time. The planned social change occurred because the government is the agent of change in the development. The unplanned social change occurred because of the flooding. The form of social change based on the time of revolution in development has led to conflict due to different interests. The adaptation of children to social changes in society tends to conformity adaptation rather than other forms of adaptation.